Theoretical structure of achievement goal orientation in sport and correlation with personality, self-efficiency and task-value - Zhu, X.; Wei, Q. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Achievement goal orientation in sports has been shown in theory and experimentally. People pay more attention to task goal orientation and ego goal orientation. This means understanding the motives from the point of approach, and neglecting the avoidance goal orientation. The purpose of this study was to introduce avoidance orientation into achievement goal theory, organizing the scale of achievement goal orientation in sport. The present paper will also discuss the structure of achievement goal orientation and the relationship between self-efficacy, personality and task values.